Evaluasi Penggunaan Antibiotik Pada Penyakit Demam Tifoid Di Puskesmas Kelua - Pawestri, Hasna; Kurniawati, Darini; Dona, Sismeri; Melviani, Melviani (Jurnal Farmasi SYIFA, 2023)
Background: Typhoid (typhoid fever) is an infectious disease caused by the bacterium Salmonella typhi. Evaluation of the use of antibiotics is carried out to find out the value of the accuracy of antibiotic therapy in terms of analysis of the right indication, the right drug, the right patient, the right dose, and alert drug side effects. Objective: Evaluate the use of antibiotics in typhoid fever at the Kelua Health Center and find out the description of the use of antibiotics in typhoid fever patients at the Kelua Health Center Methods:This type of research is descriptive observational (non-experimental) using a survey design by collecting data retrospectively. The sample in this study is 60 inpatients in October 2022 at the Kelua Health Center where sampling was using a purposive sampling method. The time for conducting the research is November 2022 to July 2023. Results: The accuracy of the use of antibiotics, namely 100% right indication, 100% right drug, 100% right patient and 100% and 100% no side effects and the type of antibiotic used in typhoid fever in the Kelua Health Center inpatient, namely cefotaxime inj. Conclusion: The results of evaluating the use of antibiotic drugs in October 2022 obtained 100% right indication, 100% right drug, 100% right patient and 100% and 100% no side effects. The type of antibiotic used for typhoid fever in the Kelua Public Health Center is inj, namely cefotaxime inj. Keywords: Evaluation, Antibiotics, Tyfoid Fever